Additives to elephant grass ensilage. IV. Sheep ruminal fermentation - de Andrade, João Batista; Lavezzo, Wagner (Pesquisa Agropecuaria Brasileira, 1998)
The ruminal fermentation patterns of sheep fed elephant grass (Pennisetum purpureum Schum.) silage enriched with ground ear corn with husks, wheat bran and saccharin in the levels 0, 8, 16 and 24% dry weight of additive/wet weight of green chop was evaluated. A split-plot randomized block design was used. The plots were the additives and their levels and the sub-plots the time of rumen fluid collection (0, 1, 3, 6, 9, 12 and 24 h after feeding). During the collection period, the sheep were fed 80% of the observed voluntary feed intake of the previous phase. For all additive types and levels used in preparing the silages, high levels of total volatile fat acids were observed, with predominance of the acetic acid. The silages having ground ear corn with husks as additive showed, in the ruminal fluid, ammonia production levels below the recommended for maximum microbial protein synthesis. However, silages with saccharin or wheat bran presented a good ammoniacal-N availability. In the ruminal fluid of the sheep fed ground ear corn with husks or wheat bran the molar proportion of butyric acid was increased and that of acetic acid and pH were decreased, as the levels of the additives in the silage increased.